Sejarah Uang, Fungsi, dan Peranannya Dalam Perkembangan Ekonomi Menurut Pakar Ekonomi Syariah - Ichsan, Atikah Nurul; Sari, Febria Lesmita; S, Syahpawi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research aims to explain the concept of money based on the Islamic economic system. This research uses a library research approach as a method of data collection by involving the understanding and study of existing theories in various relevant literature sources. The findings of this study include money based on the Islamic economic system is as a medium of exchange. The concept of money in the Islamic economic system is a flow concept. That slam does not recognize the motive of the need for money for speculation because it is not allowed or prohibited. Before money was invented, people used the barter system to meet the needs of life. In the history of money according to Islamic economics, the gold dinar and silver dirham have been authorized as official currency since the time of the prophet Muhammad SAW. Money in the Islamic economic system has a function as a means of exchange, a unit of calculation or measure of value, and a store of value.